Stereocalpin B, a New Cyclic Depsipeptide from the Antarctic Lichen Ramalina terebrata - Seulah Lee; Se Yun Jeong; Dieu Linh Nguyen; Jae Eun So; Ki Hyun Kim; Ji Hee Kim; Se Jong Han; Sung-Suk Suh; Jun Hyuck Lee; Ui Joung Youn (Metabolites, 2022)
Stereocalpin B, a new cyclic depsipeptide (1), and a new dibenzofuran derivative (3), were isolated from the Antarctic lichen, Ramalina terebrata (Ramalinaceae), along with a known cyclic depsipeptide (2). The structures of new compounds were characterized by comprehensive spectrometric analyses; high-resolution fast atom bombardment mass spectrometry (HR-FABMS) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Stereocalpin B (1) existed in a rotameric equilibrium, which was confirmed using nuclear Overhauser effect spectroscopy (NOESY)/exchange spectroscopy (EXSY) spectrum. Absolute configurations of the amino acid units in 1 were assigned using the advanced Marfey’s method and subsequent NOESY analysis of the 5-hydroxy-2,4-dimethyl-3-oxo-decanoic acid residue confirmed the complete stereochemistry of 1. Compounds 1-3 exhibited moderate antimicrobial activities against E. coli, with the IC50 values ranging from 18–30 μg/mL. Compound 2 exhibited cell growth inhibition against HCT116 cell lines, with the IC50 value of 20 ± 1.20 μM, and compounds 1 and 2 also showed potent anti-inflammatory activities against lipopolysaccharide (LPS)-induced RAW264.7 macrophages with the IC50 values ranging from 5–7 μM.